Children and Sexuality
XVIII, 371 p.
Keywords: Children and Sexuality probes the hidden relations between children and sexuality in case studies from the Greeks to the Great War. The lives reconstructed here extend from Greek Alcibiades to Lewis Carroll and Baden-Powell, each recounted with scrupulous vigilance to detail and nuance.